Scolecite - C. M. B. Line, ILL, Grenoble, France (My University, 2000)
Inelastic Neutron Scattering spectrum of Scolecite, CaAl2Si3O10.3H2O, measured on the TFXA instrument. Exact formula Ca0.1Al1.9Si3.03O10.
Keywords: TFXA